PENGARUH PARAMETER PROSES WIRE ARC ADDITIVE MANUFACTURING (WAAM) TERHADAP GEOMETRI BUTIR LAS TUNGGAL ER5356 - Deni Andriyansyah; Herianto; Emanuel Budi Raharjo; Husein Arif Susanto; Gervasius Andro Hermawan Mintardjo (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
This study examined the effects of WAAM printing parameters on single weld bead geometry using ER5356 aluminum electrode (0.1 mm diameter). Parameters varied include Voltage (18 V, 22 V, 26 V), Current (100 A, 140 A, 180 A), and Feedrate (500 mm/min, 750 mm/min, 1000 mm/min). The process produced both discontinuous and continuous weld beads. Continuous weld beads with Heat Input (HI) ranging from 0.17 kJ/mm to 0.43 kJ/mm were achieved under low voltage (18 V) and high current (180 A) settings. Voltage variation did not significantly affect bead consistency, but consistent welds were more prevalent under high-current and low-voltage conditions than with high-voltage settings. Feedrate influenced bead geometry, with lower feedrates producing larger weld grains. The smallest layer width (6.77 mm) and height (1.36 mm) were obtained with 22 V, 140 A, and 1000 mm/min, while the largest width (14.29 mm) and height (2.8 mm) resulted from 26 V, 180 A, and 500 mm/min. This study highlights the impact of voltage, current, and feedrate on weld bead geometry and consistency in WAAM processes.